Model Komunikasi Antarbudaya dalam mewujudkan Nilai-nilai Multikulturalisme melalui Kearifan Lokal Marjambar di Kelurahan Bunga Bondar Sipirok - Rezki Aulia; Rahmanita Ginting; Leylia Khairani (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
This study aims to analyze the intercultural communication model and the values of multiculturalism contained in the local wisdom of marjambar. Marjambar is a form of local wisdom in the Bunga Bondar sub-district which is carried out by the local community without any command from various parties, in its implementation, marjambar is carried out by distributing cookies typical of the local community during religious holidays, namely just before Hari Raya Eid al-Fitr performed by Muslims and one day before the New Year by Christians. To obtain the data used a qualitative descriptive research method, then in the data collection technique was done by interview, observation and documentation. The results of data collection show that the intercultural communication model occurs between communities of different ethnicities and religions. In realizing the values of multiculturalism, the community inherits a philosophy of life, "thick water is thicker and fraternal and we are one blood (alkot aek alkotan dope mudan and hitta dongan Samudar). So the conclusion is that the implementation of marjambar local wisdom reflects the value of cosmopolitan multiculturalism in it, the value of cosmopolitan multiculturalism is a value that reflects each free individual with cross-cultural lives or develops their respective cultural lives without intimidation and domination in them, so that this gives birth to a an attitude of caring between people who have different religions and ethnicities, which leads to an attitude of tolerance and harmony in society with different cultures.